Development of a mechanical strain amplifying transducer with Bragg grating sensor for low-amplitude strain sensing. (9th June 2017) - Nawrot, Urszula; Geernaert, Thomas; De Pauw, Ben; Anastasopoulos, Dimitrios; Reynders, Edwin; De Roeck, Guido; Berghmans, Francis
Abstract: Vibration-based damage identification is a well-known method to support health monitoring of civil engineering structures. Damage in such structures can be identified by measuring changes of the natural frequencies, damping factors or modal displacements of the structure. However, this approach suffers from the low sensitivity of these natural frequencies and modal displacements to certain types of damage. Modal strains and curvatures can be more sensitive to local damage, but direct monitoring of these quantities with sufficient spatial resolution is not possible with current measurement techniques due to the very small strain levels (sub-microstrain) caused by ambient or operational excitation. To deal with this issue, we propose a novel mechanical transducer equipped with an optical fiber Bragg grating (FBG) sensor that enhances the sensitivity to strain with a factor larger than 30. The principle of operation of the transducer exploits a symmetric cantilever structure that enlarges the strain experienced by the FBG sensor compared to the strain applied to the transducer itself. We carried out dynamic and static tests to verify the ability of the strain-amplifying transducers to measure small-amplitude strain levels and to evidence the potential for carrying out FBG based modal strain measurements on concrete civil engineering structures.